ANALISIS KESULITAN SISWA MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI GAYA BELAJAR - Retna Wites; Rahmi Rahmi; Hafizah Delyana (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2022)
Problem solving is one of the abilities possessed by students. The learning styles of students vary so that they affect students in solving mathematical problems. The purpose of this study was to determine the difficulties of students in solving mathematical problem solving in terms of students' learning styles. This type of research is classified as a descriptive research using a qualitative approach. The research subjects were selected by total sampling with the number of subjects as many as 20 students. Data collection techniques in this study used learning style questionnaires, problem solving tests and interviews. Technical analysis of the data in this study using the difficulty analysis guidelines. Based on the research results obtained: 1) The learning styles of students in class X IPA SMAN 13 Sijunjung majority have a visual learning style. 2) Students who have a visual learning style tend to have difficulty in performing correct mathematical procedures. 3) Students with auditory learning style tend to have difficulty in determining strategies and difficulties in performing correct mathematical procedures. 4) Students with kinesthetic learning style tend to have difficulty in translating problems into mathematical models and difficulties in performing correct mathematical procedures.